Data and derived products from airborne radar sounding survey over Devon Ice Cap, Canadian Arctic - Rutishauser, Anja; Blankenship, Donald D.; Young, Duncan A.; Wolfenbarger, Natalie S.; Beem, Lucas H.; Skidmore, Mark L.; Dubnick, Ashley; Criscitiello, Alison S.; Buhl, Dillon P.; Richter, Thomas G.; Ng, Gregory (Zenodo, 2021)
Data and derived products used in Rutishauser et al., “Radar sounding survey over Devon Ice Cap indicates the potential for a diverse hypersaline subglacial hydrological environment”, accepted for publication, The Cryosphere, https://doi.org/10.5194/tc-2021-220 Corresponding author: rutishauser.anja@gmail.com Description of datasets: ------------------------------------------ 2018_DIC_UTIG.IR2HI1B.kml Geolocation of the SRH1 profile lines. Coordinates in EPSG: 4326 - WGS 84 (latitude, longitude) ------------------------------------------ 2018_DIC_UTIG.IR2HI1B.tgz HiCARS 2 L1B echo strength profiles (radargrams) in NetCDF format. The naming of the files has the structure IR2HI1B_YYYYDOY_PST_x (e.g. IR2HI1B_2018153_DEV_JKB2t_Y87b_000.nc), where YYYY is the survey year (e.g. 2018), DOY is the survey day of the year (e.g. 153), PST is the profile name (e.g. DEV_JKB2t_Y87b), and x is the segment number if the profile was split in two (e.g. 000). For each profile, a PDF file showing the profile location and the radargram is included. ------------------------------------------ 2018_DIC_UTIG.Level2.tgz Level 2 datasets for each profile, organized in the following folders: 2018_DIC_UTIG.ILUTP2: Laser altimeter geolocated surface elevation 2018_DIC_UTIG.IR2HI2: HiCARS 2 unfocused (pik1) geolocated ice thickness, ice surface elevation, bed elevation, surface- and bed reflection coefficients, and aircraft roll 2018_DIC_UTIG.IRHFOC2: HiCARS 2 focused (foc1) geolocated ice thickness, ice surface elevation, bed elevation, surface- and bed reflection coefficients, and aircraft roll 2018_DIC_UTIG.IRSPC2: HiCARS 2 derived basal interface specularity content ------------------------------------------ Devon_basal_ice_temperature.tif: Modeled basal ice temperature [ºC] using a 1D advection diffusion model. 500 m grid cell size, coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. ------------------------------------------ Devon_bedrockDEM.tif: Digital elevation model (DEM) of the bedrock topography beneath Devon Ice Cap [m asl.]. 500 m grid cell size, coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. ------------------------------------------ Devon_gridded_RMSD_bedrock.tif : Root mean square deviation (RMDS) of the bedrock topography [m]. The RMSD was computed along each profile line, then interpolated on a 500x500m grid using the QGIS GDAL moving average grid interpolation. 500 m grid cell size, coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. ------------------------------------------ Devon_gridded_specularity.tif : Specularity content from along the profile lines interpolated on a 500x500m grid using the QGIS GDAL moving average grid interpolation. 500 m grid cell size, coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. ------------------------------------------ Devon_ice_thickness.tif : Gridded ice thickness [m] generated by subtracting the bedrock DEM from ice surface elevations derived from the ArcticDEM, Polar Geospatial Center from DigitalGlobe Inc. imagery. 500 m grid cell size, coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. ------------------------------------------ Devon_modeled_Geology.zip Devon_modeled_subglacial_geology.tif : Map of the projected geological units beneath Devon Ice Cap. The assigned numbers correspond to the following geological units: 1: pPe, 2: Cm-cf, 3: Oe, 4: Ocb, 5: Oct. Details on the geological units can be found in (Harrison et al., 2016; Mayr, 1980; Thorsteinsson & Mayr, 1987). 500 m grid cell size, coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. {pPe, Oe, Oct, Ocb,Cm_rb}_Model.stl : 3D geometry of the modeled geological units beneath Devon Ice Cap, originally published in (Rutishauser et al., 2018). Coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. Devon_load_geology_stl_files.py : Python script to load and plot the 3D geology layers in the .stl files. ------------------------------------------ Devon_subgl_hydraulic_head.tif : Subglacial hydraulic head [m] beneath Devon Ice Cap. 500 m grid cell size, coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. ------------------------------------------ Devon_subgl_hydraulic_slope.tif Slope [º] of the subglacial hydraulic head beneath Devon Ice Cap. 500 m grid cell size, coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. ------------------------------------------ Devon_subgl_lakes_brine_network.zip Devon_subgl_lake_outline.shp : Shoreline of the subglacial lakes beneath Devon Ice Cap (identified in this study). Coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. Devon_brine_network_outline.shp : Outlines of the mapped subglacial brine network beneath Devon Ice Cap. Coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. ------------------------------------------ Devon_subgl_water_routes.zip Devon_modeled_subgl_water_routes_{1, 2, 3}std.tif : Modeled subglacial water routes derived via application of a flow accumulation algorithm to the hydraulic head. The model is run 1000 times with normally distributed random errors of 1, 2 and 3 standard deviations of the hydraulic head uncertainty added to the hydraulic head (represented in the file name). Pixel values represent the model counts for which the cell has a minimum of 10 upstream cells draining into it. 500 m grid cell size, coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. Devon_extracted_subgl_water_routes.shp : Modeled subglacial water routes derived via the application of a flow accumulation algorithm to the hydraulic head. Coordinates in EPSG: 32617 - WGS 84 / UTM zone 17N. ------------------------------------------ SpecularityJustification.zip Jupyter notebook and example datafile to show the justification for the chosen specularity threshold of 0.4 for declaring a detection of possible subglacial water. ------------------------------------------ Acknowledgments The aerogeophysical survey and subsequent standard data processing were funded by the Weston Family Foundation. We also thank the G. Unger Vetlesen Foundation and the UTIG Postdoctoral Fellowship program who provided further funding for data analysis. M.L.S. was partially supported by NASA NNX16AJ64G and NASA 80NSSC20K1134. We thank PCSP and Kenn Borek Air Ltd. for logistical support, and the Nunavut Research Institute and the peoples of Grise Fjord and Resolute Bay for permission to conduct airborne surveys over Devon Ice Cap. Finally, we thank Scott Kempf for assistance with data processing, and Sam Christian and Miguel Liu-Schiaffini for help with radar reflection picking. References Harrison, J. C., Lynds, T., Ford, A., & Rainbird, R. H. (2016). Geology, simplified tectonic assemblage map of the Canadian Arctic Islands, Northwest Territories - Nunavut. Geological Survey of Canada, Canadian Geoscience , Map 80 . https://doi.org/10.4095/297416 Mayr, U. (1980). Stratigraphy and correlation of lower Paleozoic formations, subsurface of Bathurst Island and adjacent smaller islands, Canadian Arctic Archipelago. Geological Survey of Canada, Bulletin , 306 . https://doi.org/10.4095/102157 Rutishauser, A., Blankenship, D. D., Sharp, M., Skidmore, M. L., Greenbaum, J. S., Grima, C., Schroeder, D. M., Dowdeswell, J. A., & Young, D. A. (2018). Discovery of a hypersaline subglacial lake complex beneath Devon Ice Cap, Canadian Arctic. Science Advances , 4 (4), eaar4353. https://doi.org/10.1126/sciadv.aar4353 Thorsteinsson, R., & Mayr, U. (1987). The sedimentary rocks of Devon island, canadian arctic archipelago . https://doi.org/10.4095/122451